2021
DOI: 10.1111/jvim.16138
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double‐blinded clinical trial on acute transfusion reactions in dogs receiving leukoreduced versus nonleukoreduced packed red blood cells

Abstract: Background: Leukoreduction of blood products is commonly performed in human medicine, but its effect on outcome or incidence of transfusion reactions (TRs) in dogs is unknown.Objectives: To prospectively evaluate the incidence of acute TRs in, and the outcome of, dogs receiving either leukoreduced (LR) or nonleukoreduced (N-LR) packed red blood cells (PRBC).Animals: Dogs (n = 194) administered PRBC between August 2017 and June 2020.Methods: Prospective randomized double-blinded clinical trial. Dogs were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 62 publications
(151 reference statements)
1
11
1
Order By: Relevance
“…However, we believe our trial best reflects clinical practice where variably aged blood will be available for any given transfusion and therefore would provide the most relevant data regarding the effect of LR on post-transfusion inflammation. The median age of transfused RBC bags in our study was not different between groups, at 21 (14-31) days for LR and 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) days for NLR. From previous in vitro analyses, we expected accumulation of IL-8 in NLR but not in LR RBC bags over time, with the highest concentration in older NLR bags.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…However, we believe our trial best reflects clinical practice where variably aged blood will be available for any given transfusion and therefore would provide the most relevant data regarding the effect of LR on post-transfusion inflammation. The median age of transfused RBC bags in our study was not different between groups, at 21 (14-31) days for LR and 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) days for NLR. From previous in vitro analyses, we expected accumulation of IL-8 in NLR but not in LR RBC bags over time, with the highest concentration in older NLR bags.…”
Section: Discussioncontrasting
confidence: 47%
“…Finally, our study was likely underpowered to detect a between-group difference in development of FNHTR, given its low reported incidence. 6,22 Although many large retrospective studies in people have identified a significant reduction in FNHTR incidence after implementation of leukoreduction, the effect size was small. 34,35 Future studies investigating the incidence of FNHTR with…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations